A dynamic perspective on self-regulation and adaptive strategy: the advantage of a regulatory shift - Arslan, Peter-Samuel (2018)
Findings from four experiments validated the assumption that a relative change in selfregulation is the more relevant causal factor for the activation of adaptive strategies compared to an artificial attempt to manipulate an absolute state. We demonstrated that by applying the regulatory shift, which is the change from prevention focus (vigilant, avoidance, concerned with duties and responsibilities) to promotion focus (eager, approach, concerned with hopes and ideals), and vice versa. Adaptive strategies of the assimilation type (top-down, generative, productive, liberal) were enhanced by the latter focus on promotion, whilst adaptive strategies of the accommodation type (bottom-up, sensitive, re-productive, conservative) were strengthened by the latter focus on prevention. This pattern was reflected by a) the assessment of four creativity tests, b) the investigation of the endowment effect on the basis of fixed price judgments and negotiation levels, c) the assessment of the hot hand and gambler’s fallacy by means of single and serial predictions, d) a new treatment development that includes a manipulation check with the aid of a signal detection analyses (RFDrive). Although we have demonstrated a variety of operationalizations for the sake of reliability and construct validity, we have only scratched the tip of the iceberg. However, the RFDrive method offers promising possibilities to investigate and validate a broader range of boundary conditions, such as the matter of the status quo, the role of self-efficacy under uncertainty, or the impact of motivational strength. This was expecially the case under conditions of the regulatory shift. It was our aim to promote the consideration of relativity in the attempt to manipulate experimental conditions in psychological investigations. Finally, we discussed a narrowing of cognitive biases through the regulatory shift and possible transfers to work-related contexts with the focus on motivation and productivity. We hope that our aim to advance the conceptualization of self-regulation will inspire future research in the field, and beyond.